Therapeutic efficacy of omalizumab in children with moderate-to-severe allergic asthma combined with chronic sinusitis - Chong, Weikun; Li, Hailang; Wang, Juan (Frontiers in Allergy, 2023)
Background: Omalizumab has been approved for the treatment of moderate-to-severe asthma in children aged over 6 years. Its application to asthmatic children combined with other allergic diseases has been rarely explored. The present study aimed to explore the therapeutic efficacy of omalizumab on moderate-to-severe allergic asthma combined with chronic sinusitis in children. Methods: Clinical data of children diagnosed as moderate-to-severe allergic asthma combined with chronic sinusitis and treated with omalizumab from September 2020 to April 2022 were retrospectively analyzed. Lung function indexes like Childhood Asthma Control Test (C-ACT) scores, fractional exhaled nitric oxide (FeNO), and forced expiratory volume in the first second (FEV 1 ) percent predicted (FEV 1 %pred), small airway function indexes and clinical symptoms of chronic sinusitis were analyzed. Results: A total of 26 children were followed up for 16 weeks. After 16 weeks of omalizumab treatment, the significantly increased C-ACT scores (15.57±3.25 points vs. 24.98±5.21 points, F=15.7112, P<0.001) and decreased FeNO (31.55±15.57 ppb vs. 19.86±9.80 ppb, F=4.4265, P=0.0022), compared with those at baseline, were suggestive of well-controlled symptoms of asthma and improved lung function. FEV 1 %pred and FEV 1 /FVC ratio (the ratio of the forced expiratory volume in the first one second to the forced vital capacity) increased after omalizumab treatment, although no significant differences were detected (P=0.9954 and 0.9382, respectively). Peak expiratory flow (PEF) percent predicted (PEF%pred), forced expiratory flow at 75% of FVC (FEF 75% ),50% of FVC (FEF 50% ) and 25% to 75% of FVC(FEF 25-75% ) significantly increased after omalizumab treatment (P=0.0477, <0.001, <0.001, and <0.001, respectively). The Visual Analogue Scale (VAS) scores significantly decreased after omalizumab treatment (6.40±2.98 points vs. 0.85±0.40 points, t=27.2419, P<0.001), suggesting alleviation in the clinical symptoms of chronic sinusitis.In this study, omalizumab can effectively alleviate clinical symptoms, and improve lung function and quality of life in children with moderate-to-severe allergic asthma combined with chronic sinusitis.